2009
DOI: 10.1021/ol900079t
|View full text |Cite
|
Sign up to set email alerts
|

Lycojapodine A, a Novel Alkaloid from Lycopodium japonicum

Abstract: Lycojapodine A, a novel C(16)N-type Lycopodium alkaloid with an unprecedented 6/6/6/7 tetracyclic ring system, was isolated from the club moss Lycopodium japonicum. The structure and relative stereochemistry were elucidated on the basis of spectroscopic data and were further confirmed by X-ray analysis. A possible biosynthetic pathway for 1 was proposed. Its inhibitory activity on acetylcholinestrease and anti-HIV-1 activity were also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Air-dried, powdered sample (50 kg) of L. japonicum was dealt as the method reported before to obtain an base extract (67 g) [15]. This extract was subjected to a silica gel column chromatography (CC) with a gradient elution system of petroleum ether–actone (1:0–0:1) to give 7 fractions (I–VI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air-dried, powdered sample (50 kg) of L. japonicum was dealt as the method reported before to obtain an base extract (67 g) [15]. This extract was subjected to a silica gel column chromatography (CC) with a gradient elution system of petroleum ether–actone (1:0–0:1) to give 7 fractions (I–VI).…”
Section: Methodsmentioning
confidence: 99%
“…Its chemical constituents have been widely investigated and a large number of compounds have been isolated [9–14]. Our previous study on this plant reported a novel Lycopodium alkaloid, lycojapodine A [15, 16]. A continuous study on the same plant led to the isolation of three new lycopodine-type alkaloids, 4 α -hydroxyanhydrolycodoline ( 1 ), 4 α ,6 α -dihydroxyanhydrolycodoline ( 2 ), and 6- epi -8 β -acetoxylycoclavine ( 3 ), and an artifact, lycoposerramine G nitrate ( 4 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…No Lycopodium alkaloids have been reported from this plant. During our continuing search for structurally interesting and bioactive Lycopodium alkaloids [1015], two new Lycopodium alkaloids, carinatines A ( 1 ) and B ( 2 ), along with 16 known compounds, were isolated from the whole herb of P. carinatus . Carinatine A ( 1 ) was a C 16 N 2 -type Lycopodium alkaloid possessing a 5/6/6/6 ring system formed by a new C-4/C-12 bond.…”
Section: Introductionmentioning
confidence: 99%
“…], is a promising agent to treat Alzheimer’s disease with highly specific and potent inhibitory activity against acetylcholinesterase (AChE) [9]. As a consequence, these structurally complex Lycopodium alkaloids have inspired many research groups to study the chemical constituents in the Lycopodium plants [1013]. Lycopodium complanatum (L.) Holub, mainly distributed in the temperate and subtropical regions of the world [14], was used as a traditional Chinese herbal medicine for the treatment of arthritic pain, quadriplegia, and contusion [15].…”
Section: Introductionmentioning
confidence: 99%